The History Of Writing, Printing And Publishing The Holy Qur’an And Its Impact On The Arabic Language/ تاريخ كتابة المصحف الشريف وطباعته ونشره واثره في اللغة العربية - Al-Othman, Fahd Bin Abdullah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research deals with the history of writing, printing, and publishing the Holy Qur’an and its impact on the Arabic language. The descriptive research seeks to explain the stages of development of writing the Holy Qur’an from the first eras of Islam until this era. The results: Fulfilling the promise of God Almighty to preserve His Book and protect it from subtraction, addition, and distortion, to maintain the Arabic language, as the Holy Qur’an was revealed in a clear Arabic language, to shed light on the historical transformations briefly, and how the Holy Qur’an was drawn into publishing the Holy Qur’an in the Kingdom of Saudi Arabia before and after its establishment. Efforts to maintain the distribution of Quranic manuscripts have a direct impact on the spread of the Arabic language worldwide.